Respuesta :
12x^3 - 14x^2 + 8x - 2 = 2(6x^3 - 7x^2 + 4x - 1)
(4x-2) (3x^2-2x+1)
Multiply the first term from the first bracket by every term in the second bracket:
4x* 3x^2 = 12x^3
4x * -2x = -8x^2
4x * 1 = 4x
Multiply the second term from the first bracket by every term in the second bracket:
-2 * 3^2 = -6x^2
-2 * -2x = 4x
-2 * 1 = -2
Add the results together:
12x^3 + -8x^2 + 4x + -6x^2 + 4x + -2
12x^3 - 8x^2 + 4x - 6x^2 + 4x - 2
12x^3 - 8x^2 - 6x^2 + 4x + 4x - 2
12x^3 - 14x^2 + 8x - 2
Find a common factor to simplify:
Common Factor = 2
Divide everything by 2.